Preventing Loss of Independence through Exercise (PLIÉ): Evaluation of implementation at a VA community living center: Other innovative programs and practices. (7th December 2020) - Akram, Alirameen; Martin, Lynn; Lee, Maria; Nicosia, Francesca M; Martinez, Steven; Woo, Michele; Ordonez, Cherry; Lee, Jennifer Ann; Barnes, Deborah E
Abstract: Background: Preventing Loss of Independence through Exercise (PLIÉ) is an integrative group movement program developed to improve quality of life and daily function in people with mild‐to‐moderate dementia. We implemented PLIÉ at a VA Community Living Center (CLC) and conducted a formative evaluation. Methods: We provided 12 weeks of experiential training to two local clinical champions. Approximately 9 months later, we evaluated implementation based on the following outcomes: 1) reach (number of post‐training classes offered and attendance) and 2) effectiveness (anonymous surveys administered to residents, staff, and family who attended >1 class; clinical progress notes for program participants). Surveys included satisfaction ratings (5‐point Likert scale) and open‐ended questions (changes in themselves and others due to PLIÉ, what they liked most and least, and other comments). Four independent coders performed a qualitative content analysis to identify key domains of change associated with PLIÉ participation. Results: A total of 45 1‐hour PLIÉ classes were offered over 9 months. Residents attended an average of 13 +/‐ 12 classes with an average of 14 residents, 4 staff members and 2 family members per class. Anonymous survey respondents (15 residents, 14 staff, and 8 family members) were highly satisfied with the PLIÉ program (mean: 4.8, 4.4, and 4.9 on 5‐point Likert scale, respectively). Respondents reported improvements in themselves and/or others in four domains: 1) psychological, 2) physical, 3) cognitive, and 4) social. Psychological improvements included feelings of happiness/well‐being, enjoyment, and self‐empowerment. Physical improvements included mobility, strength, and energy. Cognitive improvements included engagement, communication ability, and focus/attention. Social improvements included connection, social skills, and social support. Domains identified were similar for residents, staff, family members, and clinical progress notes (Table). Negative comments were primarily related to logistics and suggesting that the class occur more frequently. Conclusion: PLIÉ was successfully implemented in a VA nursing home with high satisfaction among residents, staff and family members. Residents experienced clinically meaningful psychological, physical, cognitive, and social benefits. We are currently developing and testing an implementation training program for other CLCs and nursing homes.